Integrated Management Software for Factory Production of Modular Buildings - SungHoon Nam; DooYong Lee; BongHo Cho; KyungRai Kim (Advances in Civil Engineering)
After the first modular construction project in Korea in 2003, the scope and demand for modular systems have gradually increased. However, modular producers in Korea utilize spreadsheets to manage the process, manpower, and materials required for modular construction. This is inadequate compared to other countries that are more advanced in modular construction such as Japan and the United Kingdom. The management system in Korea decreases the effectiveness of modular construction in reducing construction time and cost. There is no formal system for managing modular production in Korea. Although some construction management programs utilized in the traditional construction industry are available, they do not reflect the flow of modular production, that is, to simultaneously produce several types of modules in accordance with demand in a factory. This research develops a modular-construction-specific production management system that has three overall functions: factory setup, project creation, and result analysis. These functions can link all the relevant data for managing modular production and can help manage several types of modules. The production management system is verified through simulation of the existing processes observed for a completed project and comparing the results to an alternative process. Through such comparisons, an optimized process design can be achieved.